Profil Clinical Scales Minnesota Multiphasic Personality Inventory-2 (MMPI-2) Adaptasi Indonesia pada Komunitas Public United not Kingdom (punk) di Kawasan Megamas Manado - Polakitang, Aprilia; Dundu, Anita; Kaunang, Theresia M.D. (e-CliniC, 2017)
Abstract: Punk community is a social phenomenon that is prevalent in major cities in Indonesia. Members of the punk community are of a certain opinion that they have discovered their concepts and their thoughts on the highlighted unique and distinctive style. This study was aimed to obtain the status of mental health among the punk community based on Minnesota multiphasic personality inventory-2 (MMPI-2) Indonesia adaptation in order to detect any possible mental disorders. This was a descriptive observational study with a cross sectional design. The study population included members of the punk community at Megamas Manado aged â‰¥18 years. The results showed that of 30 respondents, the majority were males (86.67%), aged 20-39 years (83.33%), parents worked in private sectors (43.33%), did not have a certain job (73.33%), three siblings (43.33%), stayed in Manado (16.67%), senior high school graduated, and freedom as the reason to join the community (63.33%). Distribution of the MMPI-2 clinical scales Indonesia adaptation obtained a scale with high t-scores, as follows: Pd (40%), D (16.67%), MF (6.67%). Hy G.33%), and Si (3.33%). Conclusion: There were three clinical scales with the highest psychopathology: schizophrenia, paranoia, and psychasthenia. The majority were males, senior high school graduated, and stayed in Manado.Keywords: punk community, profile, clinical scales, MMPI-2 Indonesian adaptation.Abstrak: Komunitas Punk merupakan sebuah fenomena sosial yang tengah mewabah di seluruh kota-kota besar di Indonesia. Generasi muda yang tergabung dalam komunitas punk merasa telah menemukan konsep dan pemikiran terhadap gayanya yang unik dan khas. Penelitian ini bertujuan untuk mendapatkan status kesehatan mental anggota komunitas punk berdasarkan clinical scales Minnesota multiphasic personality inventory-2 (MMPI-2) adaptasi Indonesia sebagai deteksi adanya kemungkinan gangguan mental. Jenis penelitian ialah deskriptif observasional dengan desain potong lintang. Populasi penelitian ialah anggota komunitas Punk di kawasan Megamas Kota Manado yang berusia >18 tahun ke atas. Hasil penelitian mendapatkan dari 30 responden komunitas Punk, distribusi anggota berdasarkan sosio-demografik terbanyak ialah: laki-laki (86,67%), usia 20-39 tahun (83,33%), pekerjaan orang tua di bidang swasta (43,33%), mempunyai pekerjaan tidak tetap (73,33%), bersaudara tiga orang (43,33%), beralamat di kota Manado (76,67%), pendidikan terakhir SMA (83,33%), dan alasan bergabung pada komunitas Punk karena menginginkan kebebasan (63,33%). Distribusi clinical scales MMPI-2 adaptasi Indonesia memperlihatkan skala dengan t-skor yang tinggi dengan persentase tertinggi hingga terendah sebagai berikut: Sc (90%), Pt (80%), Pa (80%), Ma 73,33%), Hy (46,67%), Pd (40%), D (16,67%), Mf (6,67%), Hy (3,33%), dan Si (3,33%). Simpulan: Terdapat tiga clinical scales yang memiliki psikopatologi tertinggi yaitu: schizophernia, paranoia, dan psychastenia. Mayoritas responden berjenis kelamin laki-laki, berpendidikan terakhir hingga SMA, dan beralamat tempat tinggal di Manado.Kata kunci: komunitas Punk, MMPI-2 adaptasi Indonesia